ANALISIS PENGARUH ETIKA KERJA ISLAMI TERHADAP KOMITMEN PROFESI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Khairul Fahmi (Universitas Islam Negeri Sumatera Utara, 2020)
This research aims to determine the influence of Islamic work ethic on a professional commitment with the organizational commitment as a intervening variable on the banker PT. Bank BRIsyariah in North Sumatera region. The data collection method used in this study is to use a questionnaire that uses a Likert scale. The population used in this study was 106 people with banker characteristics that have worked for more than 1 year. The sample in this study equals the total population of 106 samples using sampling techniques based on purposive sampling. By using the path Analysis of the research results shows that Islamic work ethics is positive and significant to the commitment of the profession of Bankers Brisyariah in North Sumatera region. The Organization's commitment is to promote the influence of Islamic work ethics on the professional commitment of bankers of BRIsyariah in North Sumatera.significant effect on the work effectiveness of the Harapan Harapan Companion Program.